2019
DOI: 10.3390/pharmaceutics11110576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactose Pseudopolymorphic Transition on the Aerosolization Performance of Drug/Carrier Mixtures

Abstract: Physico-chemical properties of lactose are key factors in adhesive mixtures used as dry powder inhaler (DPI). Despite the abundant literature on this topic, the effect of the polymorphism and pseudo-polymorphism of lactose has been seldom investigated and discussed although often lactose used in DPI is subjected to unit operations, which may alter its solid-state properties. Here, we studied the aerosolization performance of salbutamol sulphate (SS) or budesonide (BUD) formulations by investigating the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Della Bella et al [ 18 ] demonstrated the strong relationship between lactose crystal phase and aerosolization performance both with hydrophilic and lipophilic model drugs. The role of solid-state properties, such as those induced by grinding/micronization [ 19 ], on respirability performance has been evidenced by several other authors [ 5 , 8 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Della Bella et al [ 18 ] demonstrated the strong relationship between lactose crystal phase and aerosolization performance both with hydrophilic and lipophilic model drugs. The role of solid-state properties, such as those induced by grinding/micronization [ 19 ], on respirability performance has been evidenced by several other authors [ 5 , 8 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is also a stricter 90–110% requirement in the industry [ 38 ]. The novel combined carrier-based formulation (2) is also in line with the latter as SD < 5% was obtained (94.17 ± 3.34%), so homogeneity can be assumed [ 49 ]. Before the start of the stability period, the DPI capsules were filled with powders in the knowledge of specific drug content.…”
Section: Resultsmentioning
confidence: 90%
“…The industrial standard is generally more stringent, often set between 90 and 110% [54]. Our carrier-based formulations also meet the latter more stringent criteria in the blending uniformity test; thus, homogeneity can be assumed (SD < 5%) [70]. Based on the calculated drug content, the exact amount of the compositions was determined to be filled into the capsules for performing the in vitro study.…”
Section: Blend Uniformity and Drug Contentmentioning
confidence: 99%